PENGEMBANGAN MEDIA SEGITIGA PASCAL UNTUK KEMAMPUAN BERHITUNG ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA SIBORONGBORONG - Yosi Refida Siahaan; Daviq Chairilsyah; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The problems observed was that the media did not attract children`s attention, the children had difficulty in recognizing number concepts such as connecting, adding up, comparing, and jumping around in recognizing numbers. This study uses the type of research and development (RnD) in children aged 5-6 years. The research instrument is in the form of a validation sheet with data collection techniques using a questionnaire. Data analysis in this research is using descriptive validity criteria. The results of this study are that: Pascal triangle media has been developed for children aged 5-6 years by conducting two limited trials where the first limited trial was carried out before the revision of the media with the results of observations getting a score of 3 developing as expected (BSH), and the second limited trial with the results observation gets a score of 3 develops as expected. The results of the validation of the appropriate category with the average score of the validation of the first and second media experts I and II are 3,2 with a percentage of 79% and the results of the validation of the first and second media experts I andII are getting a decent category with an average score of 3,0 with a percentage of 79%. The overall results of the expert validation of educators got a score of 3,7 with a percentage of 93% getting a very decent category and validation of educator media got a score 3,5 with a percentage 89% getting a very decent category. Value observed instrument getting score of 3,0 with score 81% growing as expected (BSH).Key Words: Pascal`s Triangle, Numeracy skills, Children Aged 5-6 years